Leaf and stem anatomy, and leaf phytochemical characterization of Flaveria bidentis and F. haumanii (Asteraceae) from Santiago del Estero, Argentina - Paez, Valeria de los Angeles; Albornoz, Patricia Liliana; Lizarraga, Emilio Fernando; Sobrero, Maria Teresa; Chaila, Salvador (Instituto de Ecología, A.C., 2018)
Background and Aims: Flaveria is an American genus; two species occur in Argentina, F. bidentis and F. haumanii. Anatomical antecedents are scarce for these species and for F. bidentis the presence of uniseriate trichomes, epicuticular waxes, crystals and Kranz structure are reported. Chemically these species have diverse flavonoids of the sulphated group. The aims of this work were to characterize the leaf and cauline anatomy, and quantify the foliar phenolic components for F. bidentis and F. haumanii.Methods: The material was collected in the province of Santiago del Estero (Argentina) and subsequently fixed in FAA; conventional anatomical and phytochemical techniques were used for subsequent analysis.Key results: Both taxa presented entire leaf blade and trinervate, acrodromous primary venation. In paradermal view, both species have polyhedral epidermal cells at both surfaces, which are amphistomatic and with a striate cuticle. Presence of anomocytic, hemiparacytic, brachiparacytic, and polocytic stomata, as well as multicellular glandular trichomes. In cross section, the blade is dorsiventral with collateral vascular bundle and Kranz structure. The growing primary stem showed subepidermal angular collenchymas and amyloid sheath in the inner part of the cortex. Secondary growth included continuous xylem and phloem due to cambium activity. Parenchymal medulla was partially lignified. The presence of secretory schizogenic ducts in both blade and stem was observed. The phytochemical analysis showed higher total content of phenols, flavonoids and hydroxycinnamic acid in F. haumanii than in F. bidentis; only the total content of the ortho-dihydroxyphenols was slightly higher in the latter species.Conclusions: Flaveria bidentis and F. haumanii may be differentiated through stomata and trichome density and size and location of trichomes in the blade; whereas in both species the quantity of vascular bundles and secretory ducts of the stem are different. Quantification of phenolic compounds allowed us to establish a chemical profile for both species having scarce differences.